(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2024)
Soil chemical properties, such as Carbon and Nitrogen levels, are crucial for fulfilling the basic needs of plants. The presence of secondary and tertiary nutrients plays a vital role in constructing soil structure, influencing the survival of normal microbial flora, seeds, and later plant growth. The use of chemical fertilizers addresses nutritional deficiencies, but reports indicate that only 40% is utilized by plants, leading to soil issues like salinity and drought logging. When soil lacks essential nutrients, external amendments are necessary, impacting plant growth and crop yield by enhancing normal microbial flora i.e. Plant growth-promoting rhizobacteria (PGPRs). Recognizing the significance of both chemical nutrients and physical properties for healthy plant growth, a soil amendment called "Fertisol soil" was developed. This involved adding basic and secondary nutrients to the soil. The amended soil underwent analytical characterization and was compared with natural soil through chemical analysis and microbial growth assessments. Comparative studies using the amended soil showed improved plant growth and flowering capacity compared to control plants in terms of height and flowering. This highlights the positive impact of balanced nutrient amendments on soil health and overall plant performance.